Alpha Glucosidase Inhibitory Activity of Tiger Milk Mushroom (Lignosus rhinocerus) Ethanolic Extract - Ulfah, Mariam; Efirani, Like; Hadi, Ismanurrahman (Universitas Muhammadiyah Yogyakarta, 2024)
Tiger's milk mushroom (TMM) is a plant that can only grow in certain regions in Asia. Indonesia is the country that has the most TMM plants in the world. This plant grows wild in the forests of Kalimantan and Papua. This plant is widely used by people to treat fever, breast cancer and asthma. TMM is known to have various pharmacological activities such as anticancer. The research about TMM originate from Indonesia is still rarely carried out. So, the aim of this research is to carry out an alpha glucosidase inhibition activity test of TMM ethananolic extract. The method used for extraction the TMM is maceration method using ethanol solvent. To identify the secondary metabolite compounds from TMM, phytochemical tests and thin layer chromatography (TLC) tests were carried out. Inhibition test of alpha glucosidase enzyme activity of TMM ethanolic extract was carried using p-nitrophenyl-alpha-D-glucopyranoside reagent. The results of this phytochemical test are the ethanol extract of TMM contains flavonoid, alkaloid, terpenoid and phenolic compounds. This is confirmed by the TLC test where this test indicates the presence of flavonoid and alkaloid compounds. The results of the alpha glucosidase enzyme inhibition activity test showed that the ethanol extract of tiger milk mushrooms had an IC 50 value of 39.96 ppm which are categorized strong antidiabetic activity. From this research can be concluded that TMM ethanlolic extract very potential as an antidiabetic drug.